Leveraging Digital Accounting and Digital Taxation: Enhancing Financial Reporting Quality - Pangaribuan, Hisar; Saddam, Muhammad; Winarno, Wing Wahyu (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
By integrating advanced software and cloud-based solutions, digital accounting (DA) and digital taxation (DT) have transformed traditional accounting and tax practices. This research looks into the effects of DA and DT on financial reporting quality (FRQ) and tax compliance (TC) among Indonesian SMEs. The research employs a survey methodology, collecting data from 207 accountants and managers in Indonesian SMEs. Using Smart PLS for analysis, the study validates the constructs and tests the hypotheses. The results indicate that DA significantly enhances FRQ and directly improves TC, while DT positively affects FRQ and, through improved report quality, enhances TC. These findings highlight the dual pathways through which digital technologies influence TC directly through operational efficiencies and indirectly via improved financial reporting. This research provides empirical evidence on the synergistic effects of DA and DT in the SME context, an area that has received limited research attention, thereby contributing to the existing literature. Adopting these digital tools can lead to more accurate financial reporting and higher TC, providing valuable insights for policymakers and SME practitioners aiming to leverage digital solutions for enhanced business transparency and regulatory adherence. The study emphasizes the necessity of tailored digital strategies to realize these benefits fully